Literasi Keuangan Sebagai Usaha Untuk Mencapai Financial Well Being: Sebuah Perspektif dari Generasi Z - Syafitri, Andriati Aziizah (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2024)
Having the ability to use various types of technology, being quick in accessing information, being able to do many things at once compared to previous generations, and being responsive to social phenomena around them are some of the advantages of Generation Z growing into a generation that is intelligent, skilled, creative and critical in using technology. This effort can be started by preparing the quality of human resources from the next generation (Gen Z) to become a superior and skilled workforce. One way is to increase financial literacy so that financial prosperity can be achieved. Prosperous Society, Prosperous Country. Responding to the challenges and potential of Gen Z, researchers want to explore their views regarding the existence of the concept of financial well-being and what factors influence financial well-being. This research uses a qualitative research method using a phenomenological approach. Our research results show that Gen Z's view of financial well-being is more focused on having enough to meet their needs